2018
DOI: 10.1159/000492997
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of NF-κB by Pyrrolidine Dithiocarbamate Prevents the Inflammatory Response in a Ligature-Induced Peri-Implantitis Model: A Canine Study

Abstract: Background/Aims: The roles of toll-like receptor 4 (TLR4) and nuclear factor-kappa B (NF-κB) in peri-implantitis are unclear. Here, we used a canine model of peri-implantitis to explore the effects of inhibiting NF-κB with pyrrolidine dithiocarbamate (PDTC) on the inflammatory response in ligature-induced peri-implantitis. Methods: After successfully establishing the peri-implantitis model, beagles were randomly assigned to normal, model or PDTC groups. ELISA tests were used to determine the levels of interleu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…These results indicated that the nF-κB-mediated upregulation of TnF-α may be involved in the pathogenesis of inH/riF-induced liver injury. Several studies have shown that PdTc can prevent inflammatory injury via the inhibition of nF-κB and the subsequent downregulation of TnF-α (27,33). in the present study, it was found that the administration of PdTc reduced inflammation, suppressed NF-κB activation and resulted in the downregulation of TnF-α mrna, indicating that the anti-inflammatory action of PDTC partially contributed to liver protection.…”
Section: Parameters (Mean ± Sd) -------------------------------------supporting
confidence: 67%
“…These results indicated that the nF-κB-mediated upregulation of TnF-α may be involved in the pathogenesis of inH/riF-induced liver injury. Several studies have shown that PdTc can prevent inflammatory injury via the inhibition of nF-κB and the subsequent downregulation of TnF-α (27,33). in the present study, it was found that the administration of PdTc reduced inflammation, suppressed NF-κB activation and resulted in the downregulation of TnF-α mrna, indicating that the anti-inflammatory action of PDTC partially contributed to liver protection.…”
Section: Parameters (Mean ± Sd) -------------------------------------supporting
confidence: 67%
“…The effects of NF-kB inhibition specifically in peri-implantitis were reported in He Cy et al The study used a canine model of ligature-induced peri-implantitis and inhibited NF-kB with pyrrolidine dithiocarbamate (PDTC). The suppression of NF-kB reduced TLR4 protein expression, IL-1, IL-6, IL-8, and TNF-α production, periodontal ligament fibroblasts (PDLFs) apoptosis and induced PDLF proliferation [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…24 , 48 Briefly, macrophages could be induced into the M2 phenotype by the presence of arginine–glycine–aspartic acid (RGD) cell-binding sites in adsorbed Fn, while interaction with P1/P2 segments in absorbed Fg resulted in the generation of M1 phenotypes. 27 , 49 Hydrophilic surfaces facilitated the RGD exposure of adsorbed Fn but hindered the P1/P2 segment exposure of adsorbed Fg, 48 leading to a potentially preferential activation of macrophages toward the M2 phenotype and a modulatory effect on cytokine secretion. Therefore, the super-hydrophilic properties of H 2 -TNT surface may alter the behavior of absorbed proteins, which ultimately regulated macrophage cytokine production to reduce extended pro-inflammatory factor release and promote tissue regeneration.…”
Section: Discussionmentioning
confidence: 99%